Ecoinovação e rentabilidade: uma análise correlacional em hospedagem - Leite, Andressa Ferreira Ramalho (2021)
Tourism mobilizes the productive sectors of goods and services worldwide, requiring the work of numerous categories. The accommodation facilities sector is considered one of those basic segments of tourism, since, added to the transport segment and tourist attractions, it constitutes what is understood by tourism product. In the framework of fierce competition and the free market, with the emergence of new arrangements and business models, the importance of price for the hosting segment brings challenges to be overcome, daily, by managers. These challenges permeate the functionalities of a hotel organization chart, and permeate spaces not yet structured, but of paramount importance for the profitability of a company. In this contemporary scenario, the main objective of this work is to investigate the relationship between eco-innovation and profitability in lodging facilities, guided by the following specific objectives: a) To investigate the perception of hotel managers in Natal-RN about environmental practices in lodging; b) Identify the eco-innovation indicators in the surveyed means of accommodation; c) Check the correlation between the use of eco-innovative products and services and the profitability of the means of accommodation. The methodological assumptions applied to this work are presented, of a descriptive nature, from a historical-conceptual review of the theme, and of an exploratory nature from the research of a new fact, event or practice, such as the interrelation of the information systems. environmental management and competitiveness among the surveyed means of accommodation. The study also adopts the interpretative epistemological stance, as it aims to obtain a deep understanding of the studied themes, listing, for that, a qualitative approach to data. In this bias and for greater research reliability, a pilot test was applied among hoteliers in the city of Natal-RN, preceding the final stage of collection, where 61 respondents nationwide participated in the survey. In this step, linear regression between the average daily rate and revenue per apartment available indicators was used, in addition to an analysis of the variables based on the validation of the questionnaire scales with the calculation of Cronbach's Alpha coefficient. To consider the most important variables in the analysis of the factors, the Analysis of Variance of the main component was used. The results of this study indicate that eco-innovations appear in the current sustainable context (triple bottom line) in conjecture with the reduction of costs and construction of the image of hosting companies, thus emerging, as one of the pricing strategies, and consequently, of profitability. Seven indicators were identified with higher loads, thus explaining 71.97% of the cumulative sums of extraction of loads squared.